Challenging the 50‐50 rule for the basal‐bolus insulin ratio in patients with type 2 diabetes who maintain stable glycaemic control. Issue 2 (2nd December 2022) - Harper, Roy; Bashan, Eran; Williams, Kevin J.; Sritharan, Sajitha; Willis, Mark; Marriott, Deanna J.; Hodish, Israel
Abstract: Background: For patients using basal‐bolus insulin therapy, it is widespread clinical practice to aim for a 50‐50 ratio between basal and total daily bolus. However, this practice was based on a small study of individuals without diabetes. To assess the rule in real‐world practice, we retrospectively analyzed patients on basal‐bolus therapy that was adjusted at least weekly by an artificial intelligence‐driven titration within the d‐Nav® Insulin Management Technology. Materials and methods: We obtained de‐identified data from the Diabetes Centre of Ulster Hospital for patients with four inclusion criteria: type 2 Diabetes (T2D), on d‐Nav >6 months, on basal‐bolus insulin therapy >80% of the time (based on insulin analogs), and no gap in data >3 months. Results: We assembled a cohort of 306 patients, followed by the d‐Nav service for 3.4 ± 1.8 years (mean ± SD), corresponding to about 180 autonomous insulin dose titrations and about 5000 autonomous individual dose recommendations per patient. After an initial run‐in period, mean glycated hemoglobin (HbA1c) values in the cohort were maintained close to 7%. Surprisingly, in just over three‐quarters of the cohort, the average basal insulin fraction was <50%; in half of the cohort average basal insulin fraction <41.2%; and in one‐quarter the basal insulin fraction was <33.6%. Further, the basal insulin fraction did not remain static over time. In half of the patients, the basal insulin fraction varied by ≥1.9×; and, in 25% of the patients, ≥2.5×. Conclusion: Our data show that a 50‐50 ratio of basal‐to‐bolus insulin does not generally apply to patients with T2D who successfully maintain stable glycemia. Therefore, the 50‐50 ratio should not serve as an ongoing treatment guide. Moreover, our results emphasize the importance of at least weekly insulin titrations.